Comparison of postoperative recovery in women undergoing open abdominal hysterectomies for benign conditions observing conventional protocol versus early recovery after surgery protocol - Sharma, Surabhi; Bhardwaj , Ravikant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Benign gynaecological conditions are a significant health burden, especially in India, where hysterectomy is one of the most common surgical procedures. Despite advances in minimally invasive techniques, open abdominal hysterectomy remains prevalent. Enhanced recovery after surgery (ERAS) protocols, initially developed for gastrointestinal surgeries, have shown promising results in improving postoperative outcomes. However, their effectiveness in open abdominal hysterectomies for benign conditions is not well-documented. This study aims to compare the postoperative recovery outcomes in women undergoing open abdominal hysterectomies for benign conditions, following either the conventional protocol or the ERAS protocol. Methods: A prospective cohort study was conducted from June 2023 to May 2024 at Kamla Nehru State Hospital for Mother and Child, Shimla. Fifty women undergoing open abdominal hysterectomy for benign conditions were recruited and divided into two groups: ERAS (n=25) and conventional protocol (n=25). Key outcomes measured included hospital stay duration, time to resumption of oral intake and ambulation, postoperative pain, complications, and patient satisfaction. Results: The ERAS group demonstrated significantly shorter hospital stays (mean 5 days versus 8 days; p<0.001), faster return to oral intake (mean 6 hours versus 22 hours; p<0.001), and earlier ambulation (100% within 6-10 hours versus 0% in the conventional group; p<0.001). Postoperative complications, including nausea, vomiting, and constipation, were significantly lower in the ERAS group (p<0.05). Additionally, 56% of ERAS patients resumed normal activities within three weeks, compared to 32% in the conventional group. Patient satisfaction was also notably higher in the ERAS group. Conclusions: The ERAS protocol significantly enhances postoperative recovery in women undergoing open abdominal hysterectomy for benign conditions. It leads to shorter hospital stays, faster recovery, and higher patient satisfaction compared to conventional protocols. These findings support the broader adoption of ERAS in gynaecological surgeries.